Imposition of Criminal Sanctions Against Perpetrators of Prostitution in Indonesia - Waluyo, Adhi; Sobandi, Sobandi; Suandika, I Nyoman (CV. Syntax Corporation Indonesia, 2025)
Prostitution in Indonesia continues to be a complex and contentious issue, involving not only pimps and sex workers but also service users who remain largely unregulated by existing laws. This research examines the gaps in Indonesia’s legal framework, particularly the absence of provisions criminalizing prostitution service users. The study aims to explore how Indonesian law addresses the criminalization of all parties involved in prostitution, focusing on service users and the enforcement of criminal sanctions. Using a normative legal research methodology, this study reviews existing laws such as Law No. 44 of 2008 on Pornography, Law No. 19 of 2016 on Electronic Information and Transactions, and the Criminal Code (KUHP). It applies legal analysis through the legislative approach and legal concept approach, identifying significant gaps in applying criminal sanctions to users of prostitution services. The findings highlight that while pimps and service providers are criminalized, service users remain largely exempt from legal accountability. The study proposes that service users can be prosecuted through adultery complaints as stipulated in Article 284 of the Criminal Code. These findings suggest the urgent need for legal reforms to address this gap, ensuring a more comprehensive legal approach to prostitution regulation.